A closer look at discordant placental echogenicity: two cases under the microscope. Issue 7 (21st July 2021) - Lanna, Mariano M.; Toto, Valentina; Faiola, Stefano; Casati, Daniela; Bulfamante, Gaetano P.; Cetin, Irene; Rustico, Maria Angela
Abstract: Discordant placental echogenicity is observed in MC pregnancies complicated with twin anemia‐polycythemia sequence, but could also belong to complicated singleton gestation. Abstract : Discordant placental echogenicity is observed in MC pregnancies complicated with twin anemia‐polycythemia sequence, but could also belong to complicated singleton gestation.